Analysis of Inventory Control and Banana Chips Agroindustry Development Strategy in Bandar Lampung - M Irfan Affandi; Sussi Astuti (Agroindustrial Journal, 2017)
The study aims to analyze the performance of the inventory control and agroindustry development strategy banana chips. Site selection was done in the chips industry center Bandar Lampung City. Sampling was done offender census on members of banana agroindustry business group. Data analysis methods used was the analysis of economic order quantity (EOQ), SWOT and AHP. The results showed that the control of inventory through the ordering of raw materials and production capacity adjusted to do with intersystem messaging. The production process is generally carried out every 3 times a week with raw material price of Rp 3500,- per comb. Agroindustry development strategy banana chips were utilizing fabric of cooperation with other parties in the application of science and technology in order to produce quality products, banana chips, giving a sense of innovation so that the amount of consumer interest and increasing demand for banana chip, and optimization of infrastructure and facilities wereowned agroindustries effective and efficient.